Dynamic Transition from Branched Flow of Light to Beam Steering in Disordered Nematic Liquid Crystal - Yu, Xiao; Chang, Shan‐Shan; Wang, Zi‐Ye; Liu, Jiao; Tang, Xing‐Zhou; Chen, Jin‐Hui; Li, Bing‐Xiang; Lu, Yan‐Qing (Laser & photonics reviews, 2024)
Orientational ordered soft matter possessing diverse microstructures has become a focal point of scientific research and technological exploration, thanks to its advancements in serving as an indispensable optical platform enabling propagation of light with multidimensional and manipulatable states. Herein, a facile way is developed to manipulate the in‐plane light beam transition dynamics by harnessing a time‐variable nematic liquid crystal (NLC) film through the electrical‐field‐induced topological defects. The results show that the dynamic change of optical branched flow is associated with the growth in the correlation length of optical potential and the reduction in the density of topological defects. The optical branching can continuously transform to deterministic and tunable beam steering at the low‐defect‐density regime through annihilation kinetics of defects. The explored soft matter system provides an excellent planar platform for the fundamental physics of light interacting with topological defects and may offer new perspectives for novel optics elements toward the applications of soft matter photonics. This work realizes the continuous transformation from optical branched flow to beam steering through the electrically induced topological defects in nematic liquid crystal, which associates with the growth in the correlation length of the optical potential. The explored system provides a planar platform for the fundamental research of light‐matter interaction and enables new applications of soft matter photonics.